Sitotoksisitas Ekstrak Metanol Daun Sukun (Artocarpus Altilis), Nangka (Artocarpus Heterophyllus) Dan Kluwih (Artocarpus Camansi) Terhadap Sel Kanker Payudara Mcf-7 - Widowati, Pratiwi; , Dr. Haryoto, M.Sc (2017)
Breast cancer is one type of cancer which has high incidence rates with a fairly high percentage of deaths. Treatment of cancer is a complex treatment that typically uses chemotherapy drugs as the drug of choice. The use of chemotherapeutic agents often leads to failure in treatment because drugs develop resistance to cancer itself. This research is aimed to evaluate the cytotoxic activity of methanol extract of breadfruit, jackfruit and kluwih leaves against breast cancer cell MCF-7. The extract of breadfruit, jackfruit and kluwih leaves were obtained by maceration method using methanol. Phytochemical test was conducted by Thin Layer Chromatography with stationary phase silica GF-254 and mobile phase of ethyl acetate : n-hexane (2:8). The cytotoxic test was conducted by MTT assay with concentration of each extract 500, 250, 125, 62,5 and 31,25 µg/mL. The result of cytotoxic test was measured by ELISA reader. Tannin and alkaloids were found in phytochemical test for three extracts. Cytotoxic test demonstrate that three extracts had low cytotoxic activity against breast cancer cell MCF-7 with IC50 120,85 ; 339,46 and 530,88 µg/mL respectively for breadfruit, kluwih and jackfruit.